Malaysian Investment in Vietnam : The Case of Three Companies - Nguyen, Le Thuy Ngan (2011)
Foreign direct investment has made a substantial contribution to the economic growth in Vietnam since its opening in the early of 1990s. Among five top investors in Vietnam in the period of 1990-2010, Malaysia has emerged as a potential investor which is in ASEAN group and at adjacent level of development. In the light of that fact, this dissertation examines the influencing factors to Malaysian investment in Vietnam and the justification for their entry mode choice in this market. A case study of three Malaysian companies who have investment in Vietnam in different industries is conducted to explore the two main issues mentioned above. The results of this paper will show that Malaysian firms are strongly motivated by the objective of market expansion and the size and potential of Vietnam market. In accordance with such motives, wholly-owned subsidiary and majority joint venture are the most selected modes by Malaysian companies.